PENINGKATAN KESEHATAN HOLISTIK MELALUI EDUKASI PEMBUATAN SIROP HERBAL “SiHebat” KEPADA MASYARAKAT - Fadel, Muhammad Nurul; Besan, Emma Jayanti; Rosnarita, Intan Adevia; Yuliasari, Aulia Wahyu; Besan, Ulfa Nabila (Universitas Mataram, 2025)
The diversity of herbal plants around us is a potential that has not been optimally utilized. The Nasyiatul Aisyiyah Branch Leadership for the 2024 period requires socialization and education related to health as part of filling the routine monthly religious study activities. This community service program aims to provide education to the Nasyiatul Aisyiyah group in Getas Pejaten, Kudus Regency, regarding the production process and utilization of